Effects of Taxifolin on Osteoclastogenesis in vitro and in vivo - Cai, Cong; Liu, Changyu; Zhao, Liming; Liu, Hui; Li, Weijin; Guan, Hanfeng; Zhao, Libo; Xiao, Jun (Frontiers in Pharmacology, 2018)
Osteoporosis is a highly prevalent disease which has been a major public health problem and considered to be associated with chronic low-grade systemic inflammation and oxidative damage. Taxifolin is a natural flavonoid and possesses many pharmacological activities including antioxidant and anti-inflammatory. Because flavonoids have been confirmed to fight osteoporosis and promote bone health, the aim of this study was to investigate the effects of taxifolin on the formation and function of osteoclast. In this study, we examined the effects of taxifolin on osteoclast using both in vitro and in vivo studies. Taxifolin suppressed the activation of nuclear factor-kB, C-Fos and mitogen-activated protein kinase, and also decreased osteoclast-specific genes expression, including Trap, Mmp-9, Cathepsin K, C-Fos, Nfatc1, and Rank. Taxifolin also prevented reactive oxygen species (ROS) production following RANKL stimulation. In addition, taxifolin alleviated ovariectomized-induced bone loss by repressing osteoclast activity and decreasing serum levels of tumor necrosis factor-a, interleukin-1b, interleukin-6 and receptor activator of nuclear factor-kB ligand (RANKL) in vivo. Our results indicated that taxifolin inhibits osteoclastogenesis via regulation of modulation of several RANKL signaling pathways. Therefore, taxifolin may be considered as a potential alternative therapeutic agent for treating osteoclast-related diseases.